The effect of learning stations by computer in Acquiring some skills on the gymnastic Apparatus (floor exercise, parallel bars, and the vault) and the improvement of the students attitude to gymnastic lesson - Saleh, Shirwan; Ahmed, Saad (Journal of Physical Education, 2015)
The research aims are to to find out: 1. The effect of learning style stations using computers and the style adopted to gain some skills on devices (floor exercise, parallel bars, and the vault) and the development of students’ attitudes toward Lesson of gymnastics. 2. The differences between the experimental and control groups in gain some skills on devices (floor exercise, parallel bars, and the vault) and the development of trends towards Lesson of gymnastics. The researchers use the experimental method for suitability to the nature of the research, and research was conducted on a sample representing the students of the first school year at the Institute of Physical Education - Erbil for the academic year 2012- 2013, strong (18) students divided into two groups (experimental and control), were verified homogeneity and parity of the two sets Search variables (height, age and mass) as well as some physical fitness and motor most important elements. It has been implementing the program on 03/02/2013 until 05/04/2013 and lasted 10 weeks, and the rate of educational unit once a week for both groups, the researchers after got the data have been processed means statistical using (SPSS) program